Elevated Levels of NLRP3 in Cerebrospinal Fluid of Patients With Autoimmune GFAP Astrocytopathy - Luo, Ying; Yan, Wei; Zhou, Zheyi; Liu, Baozhu; Wang, Zhanhang; Chen, Jinyu; Wang, Honghao (Frontiers in Neurology, 2019)
Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy, a newly defined autoimmune encephalitis, is an antibody-mediated meningoencephalomyeltis. The pathogenesis of the disease is still unclear. Nod-like receptor protein 3 (NLRP3) inflammasome is a complex composed of a variety of proteins that recognizes a variety of ligands and ultimately leads to the development of inflammatory responses. This is important for infectious, inflammatory and immune diseases. The aims of this study were to detect levels of cerebrospinal fluid (CSF) NLRP3 inflammasome and inflammatory factors in autoimmune GFAP astrocytopathy patients and studied the relationships between these profiles. 20 autoimmune GFAP astrocytopathy patients, 17 viral meningoencephalitis (VM) patients and 16 controls (CTLs) were recruited. The levels of NLRP3 inflammasomes, interleukin (IL)-1β, IL-6, and IL-17 were measured by enzyme-linked immunosorbentassay (ELISA). The Expanded Disability Status Scale (EDSS) scores was used to assess the severity of clinical manifestations. The levels of NLRP3 inflammasome and inflammatory cytokines (IL-1β, IL-6, IL-17) were significantly elevated in CSF of patients with autoimmune GFAP astrocytopathy when compared with CTLs. When compared with VM patients, significantly elevated NLRP3 inflammasome was found in GFAP astrocytopathy patients, while the levels of IL-1β, IL-6, and IL-17 were not different between the two groups. Significant positive correlations were found between NLRP3 inflammasome and inflammatory cytokines and they were all positively related to the severity of the disease. Moreover, we found that patients with positive anti-GFAP antibodies had higher levels of NLRP3 and inflammatory factors. And the severity of the disease was positively correlated with GFAP antibody titers. Taken together, the results suggested that NLRP3 inflammasome was involved in the pathogenesis of autoimmune GFAP astrocytopathy. It can be used to assess the severity of the disease or acts as a new target for the therapy.